Analisis Kesadaran Keamanan Informasi Penggunaan Layanan M-Banking Menggunakan Human Aspects of Information Security Questionnaire - Ananda, Ngurah Gede Prema Satya; Saskara, Gede Arna Jude; Yudistira, Bagus Gede Krishna (Journal of Informatics, Electrical and Electronics Engineering, 2025)
This study examines the gap between information security understanding and practice among employees of the Department of Trade, Industry, Cooperatives, Small and Medium Enterprises of Buleleng Regency when using M-Banking services vulnerable to phishing. Its objective is to measure the overall level of information security awareness and identify the weakest areas to serve as a basis for more focused mitigation recommendations. This research employs a quantitative approach using a survey method involving 119 employees. The research instrument was developed based on the Human Aspects of Information Security Questionnaire (HAIS-Q) framework to measure the dimensions of Knowledge, Attitude, and Behavior. The collected data were analyzed using the Multiple Weighted Score Analysis (MWSA) method to determine vulnerability scores and rankings. The overall level of employees' information security awareness falls into the “Good” category with a composite score of 3.69. However, the findings reveal a significant knowledge-attitude-behavior gap, where the "Good" scores for Knowledge and Attitude dimensions are not matched by the Behavior dimension score, which is categorized as “Moderate.” To bridge this gap, recommendations focus on developing Standard Operating Procedures (SOPs) designed as tools to foster secure habits. For effectiveness, SOP implementation must be supported by socialization activities oriented towards behavioral change, rather than mere information dissemination. This socialization should include practical training and direct simulations, particularly phishing attack simulations.